Patterns and Severity of Injuries in Patients Following Road Traffic Accidents – A Medicolegal Aspects - Chaudhary, Archana; Wasti, Harihar (Eastern Green Neurosurgery, 2020)
Background and purpose: Road traffic accident (RTA) is the major cause of the morbidity and mortality throughout the world and the incidence is still very high in developed and developing countries. With the objective to see the pattern and severity of the injury following RTA from the medico legal point of view, this study was design in a tertiary care centre at far eastern part of Nepal. Material and method: This is a prospective analytical study with non- probability consecutive sampling of road traffic accidents cases presented in the emergency department during period of 6 months. Type of study: Prospective Analytical study. Result: There were total 210 cases of road traffic accidents with mean age of 31.8 (SD 15.7) years where majority were at 20-29 years of age group and males were the majority. Majority of the cases had injuries to the extremities followed by head. Grievous injury and life threatening injuries were also a common finding in this study. Conclusion: Road traffic accidents are more common among male, bike/scooter rider and 22-29 years of age group. Majority of the injury were fracture/dislocation of extremities and intracranial injuries. As per the medicolegal aspect, grievous and life threatening injuries were common findings among patients with road traffic accidents.